Using multiple data sources provides density estimates for endangered Florida panther. Issue 4 (23rd May 2013) - Sollmann, Rahel; Gardner, Beth; Chandler, Richard B.; Shindle, David B.; Onorato, David P.; Royle, Jeffrey Andrew; O'Connell, Allan F.
Summary: To assess recovery of endangered species, reliable information on the size and density of the target population is required. In practice, however, this information has proved hard to acquire, especially for large carnivores that exist at low densities, are cryptic and range widely. Many large carnivore species such as the endangered Florida panther Puma concolor coryi lack clear visual features for individual identification; thus, using standard approaches for estimating population size, such as camera‐trapping and capture–recapture modelling, has so far not been possible. We developed a spatial capture–recapture model that requires only a portion of the individuals in the population to be identifiable, using data from two 9‐month camera‐trapping surveys conducted within the core range of panthers in southwestern Florida. Identity of three radio‐collared individuals was known, and we incorporated their telemetry location data into the model to improve parameter estimates. The resulting density estimates of 1·51 (±0·81) and 1·46 (±0·76) Florida panthers per 100 km 2 for each year are the first estimates for this endangered subspecies and are consistent with estimates for other puma subspecies. A simulation study showed that estimates of density may exhibit some positive bias but coverage of the true values by 95% credible intervals was nominal. Synthesis and applications . This approach provides a framework for monitoring the Florida panther – and other species without conspicuous markings – while fully accounting for imperfect detection and varying sampling effort, issues of fundamental importance in the monitoring of wildlife populations. Abstract : This approach provides a framework for monitoring the Florida panther – and other species without conspicuous markings – while fully accounting for imperfect detection and varying sampling effort, issues of fundamental importance in the monitoring of wildlife populations.